Guidelines for Computer Modeling of Diabetes and Its Complications - Kahn, Richard (Diabetes care, 2004)
Decision making in medicine relies heavily on clinical studies, preferably randomized controlled clinical trials. Although the evidence obtained from such research is invaluable in guiding health care decisions, this source of information leaves many gaps. The American Diabetes Association convened a workgroup of diabetes modelers to develop guidelines on these subjects to standardize the description and validation of diabetes models. Here they focus on the steps that can be taken by model developers to ensure that others can reproduce their results and to build confidence that models are accurate, useful, and reliable tools.